Factors associated with attitudes towards HIV cure research among transgender women and travestis: a cross-sectional survey in São Paulo, Brazil - Vivian Iida Avelino-Silva; Robert J Wozniak; Natalia B Cerqueira; Maria Candida S Dantas; Bianca Mahafe; Daniel A C Barros; Edmilson Alves de Medeiros; Ana Carolina Soares de Oliveira; Thiago Sabino; Albert Roggenbuck; Carrie D Johnston; Jez L Marston; et al. (BMJ Open)
Objective Characterising the perceptions of groups most affected by HIV is fundamental in establishing guidelines for biomedical advancement. Although Brazil has successfully fought HIV/AIDS through several measures, transgender women still have a likelihood of HIV infection 55 times higher than the general population. This study aimed to better understand the perception and awareness of HIV cure research among the trans-identifying population in São Paulo, Brazil, and to determine factors that motivate or discourage participation in HIV cure studies.Setting This cross-sectional study analysed data collected from a questionnaire administered to 118 transgender women and travestis at 5 sites within the city of São Paulo. It uses quantitative methodology to describe the perspectives of transgender and travesti people in relation to HIV cure research and the context in which such perspectives are produced.Results Of 118 participants, most participants (73%) had some knowledge of HIV cure research and were most willing to participate in online surveys (52%), interviews (52%), focus groups (52%) and studies involving blood draws (57%). Those with a higher education or employment status were more likely to agree that someone had been cured of HIV, people living with HIV are discriminated against, and more information about HIV cure research is needed before the community embraces it. Only 55% of participants completely trusted their physician. The biggest motivational factors included gaining additional knowledge about HIV infection (77%) and the potential for a longer, healthier life for all (73%).Conclusions As a primary analysis of HIV cure attitudes among the transgender and travesti population as well as the social context in which they are formed, this study identifies opportunities to strengthen the dialogue and develop more educational collaborations between scientific investigators, community educators and the trans-identifying population to ensure that HIV cure research is inclusive of diverse perspectives.